Preparation of native cellulose-AgCl fiber with antimicrobial activity through one-step electrospinning. Issue 3 (11th February 2017) - Wang, Shaojun; Zhang, Xiaomin; Luo, Ting; Zhu, Jin; Su, Shengpei
Abstract: The native Cellulose-AgCl fiber have been firstly fabricated by one-step electrospinning of cellulose solution with poly(vinyl pyrrolidone) (PVP) and AgNO3 . X-ray diffraction, Scanning electron microscopy (SEM), Energy dispersive spectrometer, Thermo-gravimetric analysis and Fourier transform infrared are used to characterize the crystal structure, morphology and composition of cellulose-AgCl nanocomposites. The results of SEM indicate that the size of AgCl in cellulose fiber matrix is able to be adjusted by the addition of Polyvinylpyrrolidone (PVP). The antimicrobial activity of the nanocomposites fiber is also tested against the model microbes E. coli (Gram-negative) and S. aureus (Gram-positive). The results indicate that cellulose-AgCl nanocomposites have a good antimicrobial activity, which is improving with the decrease of AgCl size in fiber matrix. This work provides a novel and simple way to adjust the AgCl size in electrospinning cellulose matrix which can be applied as functional biomaterials.